Differential Phenotypes of Active Site and Human Autosomal Dominant Progressive External Ophthalmoplegia Mutations in Drosophila Mitochondrial DNA Helicase Expressed in Schneider Cells() - Matsushima, Yuichi (J Biol Chem, 2007)
We report the cloning and molecular analysis of Drosophila mitochondrial DNA helicase (d-mtDNA helicase) homologous to human TWINKLE, which encodes one of the genes responsible for autosomal dominant progressive external ophthalmoplegia. An RNA interference construct was designed that reduces expression of d-mtDNA helicase to an undetectable level in Schneider cells. RNA interference knockdown of d-mtDNA helicase decreases the copy number of mitochondrial DNA (mtDNA) ~5-fold. In a corollary manner, overexpression of d-mtDNA helicase increases mtDNA levels 1.4-fold. Overexpression of helicase active site mutants K388A and D483A results in a severe depletion of mtDNA and a dominant negative lethal phenotype. Overexpression of mutants analogous to human autosomal dominant progressive external ophthalmoplegia mutations shows differential effects. Overexpression of I334T and A442P mutants yields a dominant negative effect as for the active site mutants. In contrast, overexpression of A326T, R341Q, and W441C mutants results in increased mtDNA copy number, as observed with wild-type overexpression. Our dominant negative analysis of d-mtDNA helicase in cultured cells provides a tractable model for understanding human autosomal dominant progressive external ophthalmoplegia mutations.